Identification, Extraction, Phytochemical Screening and Study of Antimicrobial Activities of Native Papuan Tree Bark Extract: Dysoxylum Alliaceum and Aglaia sp. - Hadrian, Edwin; Raharja, Gabriella Lysette; Anvolia, Kelly; Insani, Rayyane Mazaya Syifa (Indonesia International Institute for Life Sciences, 2023)
Indonesia has one of the most diverse groups of ethnicities and high levels of biodiversity. Accordingly, this leads to a great wealth of ethnobotanical knowledge, where different ethnic groups develop their own methods for utilizing local plants. In Sorong, West Papua, locals often used tree barks for medication, two of which are known locally as Kayu Bawang (KB) and Kayu Teh (KT). KB and KT were morphologically identified in this study and their tree barks were extracted. Crude extracts of the tree barks were obtained via maceration using different solvents (hexane, chloroform, ethyl acetate, acetone, and methanol) with a ratio of 1:15 (w/v). Later, the extract was screened for phytochemicals (alkaloids, tannins, phlobatannins, saponins, terpenoids, flavonoids, and cardiac glycosides) followed by an assessment of antimicrobial properties. KB and KT were identified as Dysoxylum alliaceum and Aglaia sp. using the leaves, tree barks, and roots. The extraction yields of KT were highest in methanol (11.4%), while KB showed the highest yield in chloroform (1.83%). KT extracts were shown to contain all seven phytochemicals, while KB extracts lacked in tannins and flavonoids. Antimicrobial activity against E. coli and S. aureus was exhibited by 5% of KB ethyl acetate extract. These findings confirm the potential for KB and KT tree bark applications as functional food in the food industry.